Current Challenges in Teaching/Learning English for EFL Learners: The Case of Junior High School and High School. (3rd August 2015) - Akbari, Zahra
Abstract: In the 20th and 21st centuries, English has become an indispensable part of educational curriculum in Iranian schools. Despite all the efforts and investments devoted to cultivate and popularize English among Iranian language learners, the resultant outcome could not live up to the authorities' expectations. Generally speaking, the process of teaching and learning English as a foreign language in Iran is not satisfactory. A great body of research has proved that different factors are involved in this process. The researcher made an attempt to examine all the possibly existing researches which investigated/focused on the problems of teaching/learning English in Iran to elicit these factors and to scrutinize the existing problems. It is also an attempt to highlight what can be done to improve the situation significantly. A classification of these factors was suggested and it was indicated that these factors are highly interrelated.